Perlindungan Hukum Terhadap Konsumen pada Pembelian Kosmetik Secara Online dalam Perspektif Mabi’ Dalam Aqad Bai’ Salam - Eriyanti, Nahara; Fazial, Lisa (TAWAZUN: Journal of Sharia Economic Law, 2020)
This research was conducted based on problems regarding the circulation of illegal imported cosmetic products online, where consumers bought cosmetics products without BPOM distribution permit and even many fake cosmetic products that had been circulating on the online market. Article 4 letter c of Law Number 8 of 1999 concerning Consumer Protection states that consumers are entitled to true, clear and honest information about the conditions and guarantees of goods and / or services. Without a BPOM distribution permit, there is no guarantee that a cosmetic product is safe to use. But in reality, there are still business actors who do not provide clear information on a cosmetic product that is sold online and the protection of consumers now is not in accordance with what is regulated in the applicable law. Based on the description above that is the focus of research on the formulation of the problem, namely: What is the perspective of Aqad Bai's greetings on cosmetics purchases online and the legal protection of consumers? The author uses qualitative research with descriptive methods in his analysis, the data collection technique The author uses interviews / interviews. The results of the study the authors get that the Role of Law No. 8 of 1999 against consumers who are disadvantaged in the transaction of buying and selling cosmetics products online, namely providing legal protection to consumers, the protection is basically protecting the rights of consumers, Legal protection efforts undertaken by the government against consumers in illegal imported cosmetics purchase transactions online namely by carrying out prevention strategies (outreach, education), conducting surveillance strategies and implementing action strategies. As for the review of Aqad Bai 'greetings to the purchase of cosmetics online based on the analysis of the authors found in this study there are discrepancies in the Islamic view, as for the discrepancies that do not meet the requirements of the pillars namely goods. Then buying and selling cosmetic products online is invalid or null and void.